L’argumentation Rhétorique dans la Presse Franco-Algérienne - Boudounet, Naima (جامعة محمد خيضر بسكرة - كلية الآداب واللغات - مخبر وحدة التكوين والبحث في نظريات القراءة ومناهجها, 2022)
In this article, which aims to retrace the theoretical foundations emanating from the rhetorical argumentation conceived by Aristotle and resuscitated by Perelman, we have submitted chronicles belonging to the enunciative implication-commentary pole to the analysis in order to put highlighting the strategies adopted by the media authorities allowing readers to espouse the theses proposed. To show how the journalist, through speech, manages to convince his co-enunciator, a body of study formed by Pousse avec euxfromLe Soird'Algérie, Contrechamp from Liberté and Raïna Raïkoum from Le Quotidien d'Oran, illustrates that Aristotle's legacy is still relevant today
Keywords: اللغة العربية -- علم البلاغة -- فن الاقناع